2007
DOI: 10.1088/0026-1394/44/1a/04003
|View full text |Cite
|
Sign up to set email alerts
|

Results from the CII-2006 campaign at the BIPM of the BIPM.L-K11 ongoing key comparison

Abstract: Lasers from five national metrological institutes (NMIs) were brought to the BIPM in November 2006 as part of the BIPM.L-K11 ongoing key comparison initiated by the Comité Consultative des Longueurs (CCL) 11th meeting in 2003. The absolute frequency of the f component of the R(127) 11-5 transition was measured for these lasers following the Protocol for BIPM.L-K11. The results of these measurements are compiled in the present paper. The comparison reports, as communicated by each participant, are included as A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This laser meets all the recommendations (1983 and 1992) of the consultative committee for the definition of the meter [13]. Typically combined contribution to the frequency uncertainty from the parameter settings is 72.0 kHz [14]. Moreover, the He-Ne iodinestabilised laser intercomparisons from national laboratories undertaken by the BIPM (between 1993 and 2003) confirmed that the value of the laser uncertainty will not exceed 12 kHz if the laser's operating parameters are adjusted at the recommended values by the Consultative Committee of Length (CCL) as suggested in the BIPM Mise en Pratique [15].…”
Section: Experiments and Resultsmentioning
confidence: 67%
“…This laser meets all the recommendations (1983 and 1992) of the consultative committee for the definition of the meter [13]. Typically combined contribution to the frequency uncertainty from the parameter settings is 72.0 kHz [14]. Moreover, the He-Ne iodinestabilised laser intercomparisons from national laboratories undertaken by the BIPM (between 1993 and 2003) confirmed that the value of the laser uncertainty will not exceed 12 kHz if the laser's operating parameters are adjusted at the recommended values by the Consultative Committee of Length (CCL) as suggested in the BIPM Mise en Pratique [15].…”
Section: Experiments and Resultsmentioning
confidence: 67%
“…(5). While determination of the type B uncertainty was rather different task in which we considered this uncertainty value as the difference in frequency between the hyperfine structure component f of the R(127) 11-5 transition of 127 I 2 emitted from the He-Ne Iodinestabilized laser which serves as the national length standard and at the same time, the most stable laser in the country when measured through international comparisons [9,10] and when measured by the wavemeter. These values where 473612353.6026 MHz and 473612523.0000 MHz respectively.…”
Section: Uncertainty In Measurementsmentioning
confidence: 99%